Sibling experience prevents neural tuning to adult faces in 10-month-old infants. (June 2019) - Conte, Stefania; Proietti, Valentina; Quadrelli, Ermanno; Turati, Chiara; Cassia, Viola Macchi
Abstract: Early facial experience provided by the infant's social environment is known to shape face processing abilities, which narrow during the first year of life towards adult human faces of the most frequently encountered ethnic groups. Here we explored the hypothesis that natural variability in facial input may delay neural commitment to face processing by testing the impact of early natural experience with siblings on infants' brain responses. Event-Related Potentials (ERPs) evoked by upright and inverted adult and child faces were compared in two groups of 10-month-old infants with (N = 21) and without (N = 22) a child sibling. In first-born infants, P1 ERP component showed specificity to upright adult faces that carried over to the subsequent N290 and P400 components. In infants with siblings no inversion effects were observed. Results are discussed in the context of evidence from the language domain, showing that neural commitment to phonetic contrasts emerges later in bilinguals than in monolinguals, and that this delay facilitates subsequent learning of previously unencountered sounds of new languages. Highlights: P1 shows sensitivity to adult faces and upright faces in first-born infants. P1 shows no inversion nor age effects in infants with siblings. Caregiver experience induces neural tuning to adult faces in first-born infants. Sibling experience produces non-selective neural activity for upright adult faces. The variability in facial input delays neural commitment to face processing.